PEMBERIAN KONSENTRASI MOL RESALITA DAN PEMANGKASAN PUCUK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN - Nanda Oktaartah; Eko Fransisko; Rizki Septika Utami; Mardiah Apriansi; Rini Suryani (Fakultas Pertanian Universitas Ratu Samban, 2023)
Cucumber (Cucumber SativusL) is one of the types of fruit vegetable plants of the gourd family (Cucurbitaceace) originates from the continent of Asia, and is used as raw material for the beauty industry. The research was carried out from March to June 2023. and Taba Mulan Village, District/Kepahiang. This study used the Complete Randomized Block Design (RAKL) method. The first factor was the MOL concentration consisting of 5 levels. The second factor was pruning days which consisted of 5 levels and was repeated 3 times and 5 plant samples so that there were 75 pages. Giving Mol concentration and shoot pruning affected the growth and yield of cucumber plants 100 ml/water and 25 hst. In the M2P2 treatment, the fastest number of flowering ages was 85.1 days. M2P2 (50 ml/liter of water and 14 hst) had the longest fruit length, namely 61.28 cm and the M4P4 treatment (100 ml/liter of water and 25 hst) had the highest number of fruit, namely 5.4 fruit, and a small amount, namely 4.2 fruit. Keywords :Yield, Cucumber, MOL, Growth